2018
DOI: 10.1590/0104-1428.00418
|View full text |Cite
|
Sign up to set email alerts
|

PET glycolysis optimization using ionic liquid [Bmin]ZnCl3 as catalyst and kinetic evaluation

Abstract: ObstractIn the present work, the depolymerization of polyethylene terephthalate (PET) was performed by the method of glycolysis with ethylene glycol. The process was carried out using a factorial design in the Box-Behnken optimization model, using a response surface methodology (RSM) in which three factors (time, temperature and mass ratio of ethylene glycol) were studied in three levels of variation (-1, 0, +1) with two replicates of the center point, totalizing 15 experiments for which the yield of bis (2-hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…On the other hand, BHET spectra (Figure 4b) displayed highly narrow peaks indicating the crystallinity and purity of the monomer obtained after depolymerization of PET. The characteristics of BHET peaks appeared at a respective region, which was well matched with the literature reports 9,25 . More importantly, the appearance of a new intense peak at 3450 cm −1 due to the presence of hydroxyl groups in the case of BHET proved the conversion of PET into its monomer, BHET.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…On the other hand, BHET spectra (Figure 4b) displayed highly narrow peaks indicating the crystallinity and purity of the monomer obtained after depolymerization of PET. The characteristics of BHET peaks appeared at a respective region, which was well matched with the literature reports 9,25 . More importantly, the appearance of a new intense peak at 3450 cm −1 due to the presence of hydroxyl groups in the case of BHET proved the conversion of PET into its monomer, BHET.…”
Section: Resultssupporting
confidence: 88%
“…In most cases, glycolysis employs excess ethylene glycol as a reagent to break ester bonds of PET to obtain its monomer. The quality of the degradation product obtained by the glycolysis process is often much higher; as a result, it can be further reused while producing fine chemicals 9,10 . However, in the absence of the catalyst, the rate of glycolysis is very slow; hence ionic liquids‐based catalytic systems have emerged as an effective catalyst for the degradation of PET by being a green solvent with nonvolatile behavior, high thermal and chemical stability, and low inflammability 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…The melting point of unconverted PET residue was also measured and it was found that residue starts melting around 162 °C but melts completely around 168 °C corresponding to the dimer melting temperature range [ 38 ]. The melting point of BHET is in accordance as reported in various studies 109–110 [ 39 ], 111 [ 40 ] and 113.34 °C [ 41 ] via DSC-analysis. The melting point analysis is further supported by DSC analysis ( Figure S5 ) which shows that PET residue comprises only monomer and dimer peaks.…”
Section: Resultssupporting
confidence: 88%
“…Most of the homogenous catalysts (encompassing metal acetates [ 146 , 147 , 148 , 149 , 150 ], chlorides [ 151 , 152 ], alkoxides [ 46 ], hydroxides [ 153 ], carbonates [ 154 , 155 ], sulfates [ 156 ], and phosphates [ 157 ]) necessitate an additional unit operation in the chemical process, such as distillation. Zinc acetate (Zn(OAc) 2 ) has been widely employed as a catalyst for the glycolysis of PET, demonstrating its effectiveness for polyesters degradation (82 documents found on Scopus when we searched for “PET AND glycolysis AND zinc AND acetate”, March 2024).…”
Section: Glycolysis—a Way For Circular Horizonsmentioning
confidence: 99%